Social and spatial affinity drive wound care in ants - Ebi Antony George; Alba Motes-Rodrigo; Laurent Keller; Erik T. Frank (Proceedings of the National Academy of Sciences, 2026)
In social animals, open wounds pose a risk not only for the injured individual but also for its wider social context, especially when the probability of infection transmission is high. To mitigate this danger, different strategies have evolved across species, with ants representing one of the few taxa beyond humans that engage in social wound care. Yet, who provides this care and what drives care provision remains unexplored. To answer these questions, we combined controlled injury experiments with automated behavioral tracking and simulations across six colonies of the ant Camponotus fellah . Our results demonstrate that caregivers are workers in a transitional state between nursing and foraging roles, characterized by elevated activity and broad nest coverage. Being in this transitional state, however, is required but not sufficient to explain the temporal dynamics of individual care provision. Instead, care provisioning is best explained by preinjury spatial overlap, encounter rates, and social interactions, which together constitute an affinity index that predicts both the frequency and duration of subsequent wound care events. We further show that the treatment of open wounds is not the result of a generalized increase in social behaviors directed to the injured ants but part of a care response toward injuries that also involves an increase in allogrooming. Taken together, our findings reveal the necessary conditions for an individual to act as a caregiver and highlight affinity-driven dyadic interactions as an underexplored mechanism for the behavioral coordination of social immunity strategies in decentralized caste-based insect societies.